Recruitment, Training and Supervision on Employee Performance PT. Lautan Kejora Abadi Medan - Melkyory Andronicus; Markos Dinata (Jurnal Mantik, 2020)
This study aims to determine the effect of recruitment, training, and supervision. This type of research is explanatory research. The entire population is 211 employees. Due to a large number of population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 5% so that there are as many as 138 respondents in the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that recruitment, training, and supervision partially and simultaneously have a positive and significant effect on employee performance. Based on the results of this study, the implications for management are to further improve the recruitment process, better training program, and better supervision.